ANALISIS PENGANGKATAN ANAK DALAM TRADISI ADAT BATAK TOBA DI KELURAHAN TAMBUSAI TENGAH KECAMATAN TAMBUSAI KABUPATEN ROKAN HULU RIAU - Riama Silaen; Zahirman Zahirman; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was conducted based on the changes of the procedure of child adoption in Tambusai Tengah village where families are not following the customary rules of Batak Toba tradition in adopting children by not only adopting boys but also adopting more girls. Furthermore, the adoptive children are from close relatives, not-so close relatives (there are also illegitimate children), 11 families even did not ask for court decisions in the adoption process but only followed the local custom. Mangain tradition which exists in Tambusai Tengah village is not fully appropriate with the customary rules of Batak Toba tradition in which some of the rules had been changed or added. The formulation of the problem in this research is how the realization of rules and the process of child adoption are and the implementation of the position of adoptive children of the Batak Toba tradition in Tambusai Tengah village. The purpose of this research is to find out the realization of rules and the process of child adoption are and the implementation of the position of adoptive children of the Batak Toba tradition in Tambusai Tengah village. The method of this research is descriptive qualitative. The data were analyzed by data analysis technique which is the oral words and the behavior of respondents. The results of the questionnaire and interviews showed that the rules of child adoption in Tambusai Tengah village is 70.1% appropriate with the customary rules of Batak Toba tradition and the inappropriate rules is 29.9%. The implementation of the position of adoptive children is 100% accordance to the Batak Toba tradition. Furthermore, the process of children adoption in Tambusai Tengah village is 43% appropriate with the customary rules of Batak Toba tradition while 57% is inappropriate.Keywords : Children Adoption, Batak Toba Tradition